Risk Factors of Suicide Death Based on Psychological Autopsy Method; a Case-Control Study - Rasouli, Nafee; Malakouti, Seyed Kazem; Rezaeian, Mohsen; Saberi, Seyed Mehdi; Nojomi, Marzie; De Leo, Diego; Ramezani-Farani, Abbas (Archives of Academic Emergency Medicine, 2019)
Introduction: Investigation in each community can contribute to understanding the key factors involved in suicide death and its prevention. The present study aimed to investigate suicide death risk factors based on psychological autopsy method. Methods: The present case-control study was conducted from April to September 2017, in Tehran, Iran, to compare two groups of people; those who died by suicide and controls (over the age of 18 years). Data were collected by one interviewer via Structured Clinical Interviews (SCID-I), questionnaires used in the SUPREMISS study, and the Dickman impulsivity scale. Results: Each group consisted of 40 individuals. There was no significant difference between the case and control groups in terms of all demographic variables except for the level of education (p = 0.06) Â and occupational status (p = 0.009). The frequency of previous history of suicide attempt (p = 0.001), family history of suicide (p = 0.003), DSM IV Axis I disorders (p = 0.006), and substance and alcohol consumption (p = 0.01) were significantly higher in the case group. The most commonly diagnosed disorders included MDD (45%) and substance use disorders (30%), respectively. The most common methods used in suicide included hanging (32.5%), and Aluminum phosphide poisoning (32.5%) known as rice tablet. The strongest predictor of suicide death was the deceased person’s Previous history of suicide attempt (OR= 9.3; p = 0.04), smoking (OR= 6.4; p = 0.006), unemployment (OR= 5; p = 0.02), and DSM IV axis I disorders (OR= 3.8; p = 0.04). Conclusion: Previous suicide attempt, smoking, unemployment, and suffering from at least one mental disorder were the significant predictors of suicide death. Among mental disorders, major depressive disorder and substance use disorder were the most prevalent mental health problems.